Phase shift mask blank, phase shift mask, method of manufacturing phase shift mask, and method of repairing phase shift mask

JP7640293B2Active Publication Date: 2025-03-05TEKSCEND PHOTOMASK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021037722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-03-05
Estimated Expiration
2041-03-09

AI Technical Summary

Benefits of technology

【0011】 本発明の一態様に係る位相シフトマスクブランクを用いることで、位相シフトマスク上におけるヘイズの発生を十分に抑制することができ、且つ位相シフトマスクの電子線修正エッチングによる修正が容易になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640293000003
    Figure 0007640293000003
  • Figure 0007640293000004
    Figure 0007640293000004
  • Figure 0007640293000005
    Figure 0007640293000005
Patent Text Reader

Abstract

To provide: a phase-shift mask blank that is capable of sufficiently suppressing the occurrence of haze in a phase-shift film surface (on a phase-shift mask); a phase-shift mask having few haze defects and a manufacturing method therefor; and a method for modifying the phase-shift mask by electron beam modification etching.SOLUTION: A phase-shift mask blank 10 is used for making a phase-shift mask to which an exposure light having a wavelength of 200 nm or less is applied, and comprises: a transparent substrate 11; a phase-shift film 14 formed on the transparent substrate 11; and a light-shielding film 15 formed on the phase-shift film 14. The phase-shift film 14 is a multi-layer phase-shift film having a plurality of phase layers 12 and protective layers 13 alternately laminated therein. The modification etching rate for the protective layers 13 during electron beam modification is greater than that for the phase layers 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phase shift mask blank, a phase shift mask, a method for manufacturing a phase shift mask, and a method for repairing a phase shift mask, which are used in the manufacture of semiconductor devices and the like. [Background technology]

[0002] In recent years, in semiconductor processing, particularly with the increasing integration of large-scale integrated circuits, finer circuit patterns have become necessary, and there is an increasing demand for finer technology for the wiring patterns and contact hole patterns that make up the circuits. As a result, the exposure light source used in the manufacture of semiconductor devices, etc. is becoming shorter in wavelength, from KrF excimer lasers (wavelength 248 nm) to ArF excimer lasers (wavelength 193 nm).

[0003] Furthermore, as a mask with improved wafer transfer characteristics, there is, for example, a phase shift mask. In a phase shift mask, it is possible to adjust both the phase difference and the transmittance, such that the phase difference (hereinafter simply referred to as "phase difference") between the ArF excimer laser light transmitted through the transparent substrate and the ArF excimer laser light transmitted through both the transparent substrate and the phase shift film is 180 degrees, and the ratio (hereinafter simply referred to as "transmittance") of the amount of ArF excimer laser light transmitted through both the transparent substrate and the phase shift film to the amount of ArF excimer laser light transmitted through the transparent substrate is 6%.

[0004] For example, when manufacturing a phase shift mask with a phase difference of 180 degrees, a known method is to set the thickness of the phase shift film so that the phase difference is around 177 degrees, and then dry etch the phase shift film with a fluorine-based gas while simultaneously processing the transparent substrate by about 3 nm, thereby finally adjusting the phase difference to around 180 degrees.

[0005] In phase shift masks that use exposure light with a wavelength of 200 nm or less, foreign matter called "haze" gradually forms, grows, and becomes evident on the mask as a result of exposure, which can make the mask unusable. In particular, when the phase shift film is made of silicon, transition metals, and light elements such as oxygen and nitrogen, foreign matter can form on the surface of the phase shift film. Techniques for suppressing haze are described in, for example, Patent Documents 1 and 2. However, the techniques described in Patent Documents 1 and 2 may not be effective enough in suppressing the above-mentioned haze. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-173621 A [Patent Document 2] Patent No. 4579728 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in light of the above circumstances, and aims to provide a phase shift mask blank that can sufficiently suppress the occurrence of haze on the phase shift film surface (on the phase mask), a phase shift mask with few haze defects, and a method for manufacturing such a phase shift mask, as well as a correction method for such a phase shift mask by electron beam correction etching. [Means for solving the problem]

[0008] The present invention has been made to solve the above-mentioned problems. A phase shift mask blank according to one embodiment of the present invention is a phase shift mask blank used for producing a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, and comprises a transparent substrate, a phase shift film formed on the transparent substrate, and a light-shielding film formed on the phase shift film, and the phase shift film is a multilayer phase shift film formed by alternately laminating a phase difference transmittance adjusting layer that can adjust a predetermined amount of phase and transmittance for the transmitted exposure light, and a gas permeable protective layer that prevents gas from passing through the phase difference transmittance adjusting layer, and is characterized in that a correction etching rate of the gas permeable protective layer during electron beam correction is greater than that of the phase difference transmittance adjusting layer.

[0009] Moreover, a phase shift mask according to one embodiment of the present invention is a phase shift mask having a circuit pattern to which exposure light having a wavelength of 200 nm or less is applied, comprising a transparent substrate, a phase shift film formed on the transparent substrate, and a light-shielding film formed on the phase shift film, wherein the phase shift film is a multi-layer phase shift film formed by alternately stacking a plurality of phase difference transmittance adjusting layers capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, and a gas permeable protective layer preventing gas from passing through the phase difference transmittance adjusting layer, and wherein a correction etching rate of the gas permeable protective layer during electron beam correction is greater than that of the phase difference transmittance adjusting layer.

[0010] Furthermore, a method for manufacturing a phase shift mask according to one embodiment of the present invention is a method for manufacturing a phase shift mask using the above-mentioned phase shift mask blank, and is characterized in that it includes the steps of forming a light-shielding film on the phase shift film, forming a resist pattern on the light-shielding film, forming a pattern on the light-shielding film by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern, forming a pattern on the light-shielding film by fluorine-based etching (F-based) after forming the pattern on the light-shielding film, removing the resist pattern after forming the pattern on the phase shift film, and removing the light-shielding film from above the phase shift film by oxygen-containing chlorine-based etching (Cl / O-based) after removing the resist pattern. Furthermore, a method for repairing a phase shift mask according to one embodiment of the present invention is a method for repairing the above-mentioned phase shift mask by electron beam repair etching, characterized in that a surface oxidation treatment is performed on each of the gas permeable protective layers immediately before repairing the gas permeable protective layers. Effect of the Invention

[0011] By using a phase shift mask blank according to one embodiment of the present invention, the occurrence of haze on a phase shift mask can be sufficiently suppressed, and correction of the phase shift mask by electron beam correction etching becomes easy. [Brief description of the drawings]

[0012] [Figure 1] 1 is a schematic cross-sectional view showing a configuration of a phase shift mask blank according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a configuration of a phase shift mask according to an embodiment of the present invention. [Diagram 3] FIG. 13 is a schematic cross-sectional view showing side etching after electron beam correction etching of a single-layer phase shift film. [Figure 4] 4 is a schematic cross-sectional view showing side etching after electron beam correction etching of a phase shift film of a phase shift mask according to an embodiment of the present invention. FIG. [Diagram 5]1 is a schematic enlarged cross-sectional view showing side etching during electron beam correction etching of a phase shift film of a phase shift mask according to an embodiment of the present invention; [Figure 6] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a phase shift mask using a phase shift mask blank according to an embodiment of the present invention. [Figure 7] 11 is a schematic cross-sectional view showing a modified example of side etching after electron beam correction etching of a phase shift film of a phase shift mask according to an embodiment of the present invention. FIG. [Figure 8] 1A is a schematic plan view showing a structure of a phase shift mask according to an embodiment of the present invention before a repair process, and FIG. [Figure 9] 5A to 5C are schematic cross-sectional views showing a repair process of a phase shift mask according to an embodiment of the present invention. [Figure 10] 5A to 5C are schematic cross-sectional views showing a repair process of a phase shift mask according to an embodiment of the present invention. [Figure 11] 1A is a schematic plan view showing a structure of a phase shift mask after a repair process according to an embodiment of the present invention, and FIG. 1B is a schematic cross-sectional view showing the structure of the phase shift mask after a repair process according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The inventors of the present application considered that the occurrence of haze in a mask blank or mask can be reduced if all three elements, namely, the constituent material of a phase adjustment film (a phase difference transmittance adjusting layer described later) constituting a phase shift mask blank or a phase shift mask, an oxidizing gas such as water or oxygen, and exposure energy, are present, and therefore the phase shift mask blank or phase shift mask is configured as follows. That is, the phase shift mask blank, phase shift mask, and manufacturing method thereof according to this embodiment are based on the technical idea of ​​providing a gas protection layer (a so-called gas barrier layer) on the phase adjustment film to prevent the oxidizing gas from coming into contact with the constituent material of the phase adjustment film, thereby reducing the occurrence of haze.

[0014] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the schematic cross-sectional views do not accurately reflect the actual dimensional ratio or the number of patterns, and the amount of engraving in the transparent substrate and the amount of damage to the film are omitted. Suitable embodiments of the phase shift mask blank of the present invention include the following.

[0015] (Overall structure of phase shift mask blank) FIG. 1 is a schematic cross-sectional view showing the configuration of a phase shift mask blank according to an embodiment of the present invention. The phase shift mask blank 10 shown in FIG. 1 is a phase shift mask blank used for producing a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, and includes a substrate (hereinafter, also simply referred to as "substrate") 11 transparent to the exposure wavelength, and a phase shift film 14 formed on the substrate 11. The phase shift film 14 is a multi-layer phase shift film in which a phase difference transmittance adjusting layer (hereinafter, also simply referred to as "phase layer") 12 capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, and a gas permeable protective layer (hereinafter, also simply referred to as "protective layer") 13 formed on the phase difference transmittance adjusting layer 12 and preventing gas from permeating the phase difference transmittance adjusting layer 12 are alternately laminated. The correction etching rate of each protective layer 13 during electron beam correction is larger than that of each phase layer 12. The bottom layer of the phase shift film 14, i.e., the layer closest to the substrate 11, is preferably the phase layer 12. The top layer of the phase shift film 14, i.e., the layer farthest from the substrate 11, is preferably the protective layer 13. Each layer constituting the phase shift mask blank 10 according to the embodiment of the present invention will now be described in detail.

[0016] (substrate) There is no particular limitation on the substrate 11. The substrate 11 may be, for example, quartz glass or CaF 2 Alternatively, aluminosilicate glass or the like is generally used.

[0017] (Phase shift film) The phase shift film 14 is a multi-layer phase shift film in which phase layers 12 and protective layers 13 are alternately laminated in this order, and is formed on the substrate 11 with or without other films interposed therebetween. The phase shift film 14 is, for example, a film that is resistant to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

[0018] The transmittance value of the phase shift film 14 is, for example, within a range of 3% to 80% relative to the transmittance of the substrate 11, and an optimal transmittance can be appropriately selected according to a desired wafer pattern. The phase difference value of the phase shift film 14 is, for example, within a range of 160 degrees to 220 degrees, and more preferably within a range of 175 degrees to 190 degrees. That is, the phase shift film 14 may have a transmittance to the exposure light within a range of 3% to 80% and a phase difference within a range of 160 degrees to 220 degrees. When the transmittance of the phase shift film 14 to the exposure light is less than 3%, good exposure performance may not be obtained. When the phase difference is within a range of 160 degrees to 220 degrees, the required exposure performance can be easily maintained.

[0019] <Phase layer> The phase layer 12 is formed on the substrate 11 or the protective layer 13 with or without other films, and is a layer that can adjust the phase and transmittance of the transmitted exposure light by a predetermined amount. Here, "adjusting the phase" means, for example, inverting the phase. Also, "transmittance" means the transmittance of the exposure light. Moreover, the phase layer 12 is a layer that is resistant to oxygen-containing chlorine-based (Cl / O-based) gas etching, can be etched with a fluorine-based gas (F-based), and can be repaired by an EB (electron beam) repair method. The phase layer 12 is, for example, a single layer film containing silicon and at least one selected from transition metals, nitrogen, oxygen, and carbon, or a multilayer film or gradient film thereof, and the transmittance and phase difference for the exposure wavelength are adjusted by appropriately selecting the composition and film thickness. Here, the "gradient film" refers to a film in which the composition ratio of the components (materials) constituting the phase layer 12 is not uniform throughout the phase layer 12, but changes at a constant rate.

[0020] The phase layer 12 preferably contains silicon in the range of 20 atomic % to 60 atomic % in the element ratio of the entire phase layer 12, preferably contains transition metals in the range of 0 atomic % to 20 atomic % in the element ratio of the entire phase layer 12, preferably contains nitrogen in the range of 30 atomic % to 80 atomic % in the element ratio of the entire phase layer 12, preferably contains oxygen in the range of 0 atomic % to 30 atomic % in the element ratio of the entire phase layer 12, and preferably contains carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire phase layer 12. The more preferable content range of each element in the phase layer 12 is 30 atomic % to 50 atomic % in the element ratio of silicon, 0 atomic % to 10 atomic % in the element ratio of the entire phase layer 12, 40 atomic % to 70 atomic % in the element ratio of the entire phase layer 12, 0 atomic % to 20 atomic % in the element ratio of the entire phase layer 12, and 0 atomic % to 5 atomic % in the element ratio of the entire phase layer 12. If the content of each element in the phase layer 12 is within the above numerical range, the phase difference as well as the transmittance of the phase layer 12 can be easily controlled. The phase layer 12 may contain at least one of oxide, carbide, and nitride of a metal silicide. In this case, the metal constituting the metal silicide may be a transition metal, which will be described later.

[0021] The transition metal contained in the phase layer 12 is preferably at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, and more preferably molybdenum. If the transition metal contained in the phase layer 12 is at least one selected from molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium, the processing of the phase layer 12 becomes easy, and if it is molybdenum, the processing of the phase layer 12 such as etching becomes even more excellent.

[0022] The thickness of each phase layer 12 is preferably 0.5 nm or more, and the total thickness of each phase layer 12 is preferably greater than the total thickness of each protective layer 13. If the thickness of each phase layer 12 is less than 0.5 nm, it is difficult to obtain the effect of phase shift. In addition, the thickness of the phase layer 12 is preferably 0.5 nm or more, taking into consideration the film formation limit of the phase layer 12 in a film formation method such as sputtering. In addition, if the total thickness of each phase layer 12 is thinner than the total thickness of each protective layer 13, the proportion of the phase layer 12 in the entire phase shift film 14 becomes relatively small, and as a result, it is difficult to obtain the effect of phase shift. The thickness of the phase layer 12 may be different for each layer or may be the same. When the thickness of the phase layer 12 is different for each layer, it is easy to adjust the total thickness of the phase layers 12. When the thickness of the phase layer 12 is the same for each layer, the accuracy of the total thickness of the phase layers 12 is improved.

[0023] As described above, the phase shift film 14 includes a plurality of phase layers 12, and the film type (type and composition ratio of constituent materials) of the phase layers 12 may be different for each layer or may be the same. For example, the type of transition metal contained in the phase layers 12 may be different for each layer or may be the same for each layer. When the type of transition metal contained in the phase layers 12 is different for each layer, a specific function can be imparted to each layer, that is, a function can be separately imparted to each layer. When the type of transition metal contained in the phase layers 12 is the same for each layer, the film formation conditions for each phase layer 12 are the same, so that the film quality (physical properties) of each phase layer 12 becomes uniform.

[0024] <Protective layer> The protective layer 13 is formed on the phase layer 12 with or without another film interposed therebetween, and is a layer for preventing or suppressing gas permeation (particularly, permeation of oxidizing gases such as water and oxygen) into the phase layer 12, i.e., a gas barrier layer. This embodiment can prevent or suppress the intrusion of gas, which is considered to be one of the factors that cause haze, into the phase layer 12, and therefore, when the mask is used for a long period of time (for example, when the dose on the mask is 100 kJ / cm 2 Even if the exposure temperature exceeds 100° C., the generation of haze on the surface of the phase shift mask can be prevented or suppressed. The gas (atmospheric gas) whose permeation is prevented or suppressed by the protective layer 13 is an oxidizing gas, specifically, oxygen-containing molecules, and more specifically, water molecules.

[0025] The protective layer 13 is a layer that is resistant to oxygen-containing chlorine-based (Cl / O-based) gas etching, can be etched with a fluorine-based gas (F-based), and can be repaired by an EB (electron beam) repair method. The protective layer 13 is preferably a single layer film made of one or more compounds selected from tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, and tellurium compounds, or a mixed film or multi-layer film of these compounds, but the composition is not particularly limited as long as it is a layer having a barrier function. Note that the above-mentioned tantalum metal, tungsten metal, and tellurium metal refer to the simple substance of each metal.

[0026] The protective layer 13 made of a tantalum compound is a single layer film containing tantalum and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 13 made of a tantalum compound preferably contains tantalum in the range of 10 atomic % to 90 atomic % in the entire element ratio of the protective layer 13, preferably contains oxygen in the range of 0 atomic % to 90 atomic % in the entire element ratio of the protective layer 13, preferably contains nitrogen in the range of 0 atomic % to 70 atomic % in the entire element ratio of the protective layer 13, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the entire element ratio of the protective layer 13. More preferable content ranges of each element in the protective layer 13 made of a tantalum compound are tantalum in the range of 20 atomic % to 80 atomic % in the entire element ratio of the protective layer 13, oxygen in the range of 0 atomic % to 80 atomic % in the entire element ratio of the protective layer 13, nitrogen in the range of 0 atomic % to 60 atomic % in the entire element ratio of the protective layer 13, and carbon in the range of 0 atomic % to 10 atomic % in the entire element ratio of the protective layer 13. If the content of each element in the protective layer 13 made of a tantalum compound is within the above numerical range, the barrier property of the protective layer 13 against gas permeation into the phase layer 12 is improved.

[0027] Moreover, the protective layer 13 made of a tungsten compound is a single layer film containing tungsten and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 13 made of a tungsten compound preferably contains tungsten in the range of 10 atomic % to 70 atomic % in the element ratio of the entire protective layer 13, preferably contains oxygen in the range of 30 atomic % to 90 atomic % in the element ratio of the entire protective layer 13, preferably contains nitrogen in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 13, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 13. More preferable content ranges of each element in the protective layer 13 made of a tungsten compound are tungsten in the range of 20 atomic % to 60 atomic % in the element ratio of the entire protective layer 13, oxygen in the range of 50 atomic % to 80 atomic % in the element ratio of the entire protective layer 13, nitrogen in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 13, and carbon in the range of 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 13. If the content of each element in the protective layer 13 made of a tungsten compound is within the above numerical range, the barrier property of the protective layer 13 against gas permeation to the phase layer 12 is improved.

[0028] The protective layer 13 made of a tellurium compound is a single layer film containing tellurium and one or more elements selected from oxygen, nitrogen, and carbon, or a multilayer film or gradient film thereof. The protective layer 13 made of a tellurium compound preferably contains tellurium in the range of 20 atomic % to 70 atomic % in the element ratio of the entire protective layer 13, preferably contains oxygen in the range of 30 atomic % to 90 atomic % in the element ratio of the entire protective layer 13, preferably contains nitrogen in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 13, and preferably contains carbon in the range of 0 atomic % to 20 atomic % in the element ratio of the entire protective layer 13. More preferable content ranges of each element in the protective layer 13 made of a tellurium compound are 30 atomic % to 60 atomic % in the element ratio of the entire protective layer 13, 50 atomic % to 80 atomic % in the element ratio of the entire protective layer 13, 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 13, and 0 atomic % to 10 atomic % in the element ratio of the entire protective layer 13. If the content of each element in the protective layer 13 made of a tellurium compound is within the above numerical range, the barrier property of the protective layer 13 against gas permeation to the phase layer 12 is improved.

[0029] As described above, if the protective layer 13 is a single layer film made of one or more compounds selected from tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, and tellurium compounds, or a mixed film or multi-layer film of these compounds, it can effectively prevent gas permeation into the phase layer 12. The thickness of each protective layer 13 is preferably 0.5 nm or more, and the total thickness of each protective layer 13 is preferably 30 nm or less. If the thickness of each protective layer 13 is less than 0.5 nm, the thickness of the protective layer 13 is too thin, and the possibility of the gas barrier property being reduced increases. In addition, the thickness of the protective layer 13 is preferably 0.5 nm or more, taking into consideration the film formation limit of the protective layer 13 in a film formation method such as sputtering. In addition, if the total thickness of each protective layer 13 exceeds 30 nm, the proportion of the phase layer 12 in the entire phase shift film 14 becomes relatively small, and as a result, it becomes difficult to obtain the effect of the phase shift.

[0030] Furthermore, the thickness of the protective layer 13 may be different for each layer or may be the same. When the thickness of the protective layer 13 differs for each layer, it is easy to adjust the total thickness of the protective layers 13. When the thickness of the protective layer 13 is the same for each layer, the accuracy of the total thickness of the protective layers 13 is improved. As described above, the phase shift film 14 includes a plurality of protective layers 13, and the film type (type and composition ratio of constituent materials) of each protective layer 13 may be different or the same for each layer. For example, the type of metal element contained in each protective layer 13 may be different or the same for each layer. When the type of metal element contained in each protective layer 13 is different for each layer, a specific function can be imparted to each layer, that is, a function can be separately imparted to each layer. When the type of metal element contained in each protective layer 13 is the same for each layer, the film formation conditions for each protective layer 13 are the same, so that the film quality (physical properties) of each protective layer 13 becomes uniform.

[0031] (Overall structure of phase shift mask) The configuration of a phase shift mask 100 according to an embodiment of the present invention will now be described. 2 is a schematic cross-sectional view showing the configuration of a phase shift mask according to an embodiment of the present invention. The phase shift mask 100 shown in FIG. 2 is a phase shift mask (i.e., a patterned phase shift mask) to which exposure light having a wavelength of 200 nm or less is applied and which has a circuit pattern, and includes a substrate 11 transparent to the exposure wavelength and a phase shift film 14 formed on the substrate 11. The phase shift film 14 is a multi-layer phase shift film in which a phase layer 12 capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light and a protective layer 13 formed on the phase layer 12 and preventing gas from passing through the phase layer 12 are alternately laminated in a plurality of layers. The correction etching rate of each protective layer 13 during electron beam correction is larger than that of each phase layer 12. The bottom layer of the phase shift film 14, i.e., the layer closest to the substrate 11, is preferably the phase layer 12. The top layer of the phase shift film 14, i.e., the layer farthest from the substrate 11, is preferably the protective layer 13.

[0032] Phase shift mask 100 includes a phase shift film pattern 17 formed by removing a portion of phase shift film 14 to expose the surface of substrate 11 . The composition of each layer constituting the phase shift mask 100 according to an embodiment of the present invention is the same as the composition of each layer constituting the phase shift mask blank 10 according to the embodiment of the present invention described above, and therefore detailed explanations of the composition of each layer will be omitted.

[0033] 3 is a schematic cross-sectional view showing the shape of the phase shift film 14 (phase layer 12) after electron beam correction etching when the phase shift film 14 is made of only a single phase layer 12. The electron beam correction etching is performed using, for example, a fluorine-based gas (a gas consisting of xenon and fluorine, XeF 2 While supplying an etching gas such as fluorine-based gas, the material constituting the phase shift film 14 (phase layer 12) is irradiated with an electron beam to etch the area to be etched, thereby promoting the reactivity of the fluorine etchant. However, the material constituting the phase layer 12 has a high etching resistance against the above-mentioned fluorine-based gas, and etching takes an extremely long time, so damage occurs in a direction perpendicular to the etching direction (direction from the surface side of the phase layer 12 toward the substrate 11 side) (in-plane direction of the phase layer 12), called side etching BS, as shown in Figure 3. If this side etching is large, the line width of the area etched by the electron beam correction is significantly different from the expected line width, which is one of the reasons for the failure of the correction.

[0034] In addition, the "side etching amount (side etching width) BW" shown in FIG. 3 refers to the distance from the convex portion to the concave portion in the in-plane direction of the phase layer 12 on the side surface of the phase layer 12 on which the phase shift film pattern 17 is formed, that is, the side surface in contact with the electron beam correction etching portion 17b, when the most protruding portion in the in-plane direction of the phase layer 12 is the convex portion and the most recessed portion in the in-plane direction of the phase layer 12 is the concave portion. In FIG. 3, the above-mentioned convex portion corresponds to the portion of the phase layer 12 in contact with the substrate 11, and the above-mentioned concave portion corresponds to the surface portion of the phase layer 12. The side etching amount BW according to the embodiment of the present invention is preferably 5 nm or less. If the side etching amount BW is 5 nm or less, the deterioration of the transfer performance can be reduced.

[0035] In this embodiment, as shown in FIG. 4, a phase shift film 14 is used in which a protective layer 13 having a relatively faster etching rate for electron beam correction compared to the material constituting the phase layer 12 and a phase layer 12 having a relatively slow etching rate for electron beam correction compared to the material constituting the protective layer 13 are alternately laminated, thereby suppressing side etching BS and improving the success rate of electron beam correction etching.

[0036] The detailed mechanism will be described below with reference to FIG. 5, which shows an enlarged view of a part of the phase shift film 14. 5 is a diagram showing the protective layer 13 located inside the phase shift film 14 being subjected to electron beam correction etching, and BH is a protective layer (etching resistant film) formed on the side of the phase layer 12. When the phase shift film 14 of this embodiment is subjected to electron beam correction etching, it is preferable to use a multi-stage etching process in which the etching gas is switched between the protective layer 13 and the phase layer 12, but an etching process in which the etching gas is not switched between the protective layer 13 and the phase layer 12 may also be used. When the phase layer 12 and the protective layer 13 are etched with one type of etching gas, a fluorine-based gas (e.g., XeF 2 For the phase layer 12, the above-mentioned fluorine-based gas (e.g., XeF 2) has a weak function as an etching gas and acts as a deposition gas, so it is very unlikely to etch the phase layer 12 and forms a protective layer BH on the side of the phase layer 12. Therefore, by using a phase shift film 14, which is a multilayer phase shift film in which a protective layer 13 and a phase layer 12 are laminated, electron beam correction etching that suppresses the occurrence of side etching BS can be achieved, as shown in Figure 4.

[0037] In this embodiment, the correction etching rate when only the protective layer 13 is corrected by electron beam may be within a range of 1 to 10 times, preferably within a range of 4 to 8 times, and more preferably within a range of 5 to 7 times, of the correction etching rate when only the phase layer 12 is corrected by electron beam. If the correction etching rate when only the protective layer 13 is corrected by electron beam is within the above numerical range, the time required for the electron beam correction can be effectively shortened compared to the conventional technology. In this embodiment, the correction etching rate when only the phase layer 12 is corrected by electron beam is preferably 2.5 nm / min or more, more preferably 3.0 nm / min or more, and even more preferably 3.5 nm / min or more. If the correction etching rate when only the phase layer 12 is corrected by electron beam is within the above numerical range, the time required for the electron beam correction can be effectively shortened compared to the conventional technology.

[0038] The protective layer BH is, for example, a layer formed of at least one of an oxide film, a nitride film, an oxynitride film, and a carbide film containing one or more compounds selected from tantalum metal, a tantalum compound, a tungsten metal, a tungsten compound, a tellurium metal, and a tellurium compound. That is, in this embodiment, the protective layer BH may further have a composition different from that of the phase layer 12, and cover at least a part of the side surface of the phase layer 12 on which the phase shift film pattern 17 is formed to protect the side surface of the phase layer 12.

[0039] In this embodiment, when performing electron beam correction etching, the surface oxidation treatment of the protective layer 13 may be performed for each layer of the protective layer 13 immediately before the electron beam correction etching of each protective layer 13. That is, in this embodiment, when performing electron beam correction etching, the surface oxidation treatment of the protective layer 13 may be first performed, the protective layer 13 after the surface oxidation treatment is subjected to electron beam correction etching, the phase layer 12 located below the protective layer 13 after the electron beam correction etching is then subjected to electron beam correction etching, and the protective layer 13 located below the phase layer 12 after the electron beam correction etching is then subjected to surface oxidation treatment.

[0040] (Method of manufacturing phase shift mask) A method for manufacturing a phase shift mask 100 using the phase shift mask blank 10 of this embodiment includes the steps of forming a light-shielding film 15 on a phase shift film 14, forming a resist pattern 16 on the light-shielding film 15 formed on the phase shift film 14, forming a pattern in the light-shielding film 15 by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern 16, forming a pattern in the light-shielding film 15 by fluorine-based etching (F-based) after forming the pattern in the light-shielding film 15, removing the resist pattern 16 after forming the pattern in the phase shift film 14, and removing the light-shielding film 15 from above the phase shift film 14 by oxygen-containing chlorine-based etching (Cl / O-based) after removing the resist pattern 16. Here, the light-shielding film 15 according to the embodiment of the present invention will be described.

[0041] <Light-shielding film> The light-shielding film 15 is a layer formed on the phase shift mask blank 10 (protective layer 13) according to the embodiment of the present invention described above. The light-shielding film 15 is, for example, a single layer film made of chromium alone or a chromium compound, or a multilayer film or gradient film thereof. More specifically, the light-shielding film 15 made of a chromium compound is a single layer film containing chromium and one or more elements selected from nitrogen and oxygen, or a multilayer film or gradient film thereof.

[0042] The light-shielding film 15 made of a chromium compound preferably contains chromium in the range of 30 atomic % to 100 atomic % inclusive, oxygen in the range of 0 atomic % to 50 atomic % inclusive, nitrogen in the range of 0 atomic % to 50 atomic % inclusive, and carbon in the range of 0 atomic % to 10 atomic % inclusive, in terms of the element ratio of the entire light-shielding film 15. More preferred content ranges of each element in the light-shielding film 15 made of a chromium compound are 50 atomic % to 100 atomic % inclusive for chromium, 0 atomic % to 40 atomic % inclusive for oxygen, 0 atomic % to 40 atomic % inclusive for nitrogen, and 0 atomic % to 5 atomic % inclusive for carbon, in terms of the element ratio of the entire light-shielding film 15. If the content of each element in the light-shielding film 15 made of a chromium compound is within the above numerical range, the light-shielding property of the light-shielding film 15 is enhanced.

[0043] The thickness of the light-shielding film 15 is preferably, for example, in the range of 35 nm to 80 nm, particularly in the range of 40 nm to 75 nm. The light-shielding film 15 can be formed by a known method. A preferred method for obtaining a film with excellent uniformity most easily is a sputtering film formation method, but the present embodiment is not limited to the sputtering film formation method.

[0044] The target and the sputtering gas are selected according to the film composition. For example, a method for forming a film containing chromium can be exemplified by using a target containing chromium and performing reactive sputtering in only an inert gas such as argon gas, only a reactive gas such as oxygen, or a mixed gas of an inert gas and a reactive gas. The flow rate of the sputtering gas can be adjusted according to the film characteristics, and may be constant during film formation, or may be changed according to the desired composition when the amount of oxygen or nitrogen is to be changed in the thickness direction of the film. In addition, the power applied to the target, the distance between the target and the substrate, and the pressure in the film formation chamber may be adjusted.

[0045] In addition, when the light-shielding film 15 according to the present embodiment is the above-mentioned multi-layer film, the thickness of each layer may be different or the same. For example, when the light-shielding film 15 has a two-layer structure of a lower-layer light-shielding film (not shown) formed on the phase shift mask blank 10 (protective layer 13) side and an upper-layer light-shielding film (not shown) formed on the lower-layer light-shielding film, the thickness of the lower-layer light-shielding film may be thicker or thinner than the thickness of the upper-layer light-shielding film. Furthermore, when the light-shielding film 15 according to this embodiment is a multi-layer film, the film types (types and composition ratios of constituent materials) may be different for each layer or may be the same.

[0046] Each step of the method for manufacturing the phase shift mask 100 according to the embodiment of the present invention will now be described in detail. FIG. 6 is a schematic cross-sectional view showing a manufacturing process of a phase shift mask 100 using the phase shift mask blank 10 shown in FIG. 1. FIG. 6(a) shows a process of forming a light-shielding film 15 on a phase shift film 14. FIG. 6(b) shows a process of applying a resist film on the light-shielding film 15, drawing, and then performing a development process to form a resist pattern 16. FIG. 6(c) shows a process of patterning the light-shielding film 15 by oxygen-containing chlorine-based dry etching (Cl / O-based) along the resist pattern 16. FIG. 6(d) shows a process of patterning the phase shift film 14 by fluorine-based etching (F-based) along the pattern of the light-shielding film 15 to form a phase shift film pattern 17. FIG. 6(e) shows a process of peeling and removing the resist pattern 16 and then cleaning it. FIG. 6(f) shows a process of removing the light-shielding film 15 by oxygen-containing chlorine-based etching (Cl / O-based) from above the phase shift film 14 on which the phase shift film pattern 17 has been formed. In this way, the phase shift mask 100 according to this embodiment is manufactured.

[0047] The phase shift mask 100 according to the present embodiment is a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, and includes a substrate 11 and a phase shift film 14 formed on the substrate 11 with or without other films. The phase shift film 14 is a multi-layer phase shift film in which a phase layer 12 capable of adjusting a predetermined amount of phase and transmittance for the transmitted exposure light, and a protective layer 13 formed on the phase layer 12 and preventing gas from passing through the phase layer 12 are alternately laminated in a plurality of layers. The correction etching rate of each protective layer 13 during electron beam correction is greater than that of each phase layer 12. The phase shift mask 100 also includes a phase shift film pattern 17 formed by removing a portion of the phase shift film 14 so that a portion of the substrate 11 is exposed.

[0048] In the step of FIG. 6(b), either a positive resist or a negative resist can be used as the material of the resist film, but it is preferable to use a chemically amplified resist for electron beam writing, which enables the formation of a highly accurate pattern. The thickness of the resist film is, for example, in the range of 50 nm to 250 nm. In particular, when producing a phase shift mask that requires the formation of a fine pattern, in order to prevent the pattern from collapsing, it is necessary to make the resist film thin so that the aspect ratio of the resist pattern 16 does not become large, and a thickness of 200 nm or less is preferable. On the other hand, the lower limit of the thickness of the resist film is determined by comprehensively considering conditions such as the etching resistance of the resist material used, and is preferably 60 nm or more. When a chemically amplified resist for electron beam writing is used as the resist film, the energy density of the electron beam during writing is 35 μC / cm 2 to 100μC / cm 2 After this drawing, a heat treatment and a development treatment are performed to obtain a resist pattern 16.

[0049] In the step of FIG. 6(e), the resist pattern 16 may be removed by wet stripping using a stripping liquid, or by dry stripping using dry etching. 6(c), the conditions of the oxygen-containing chlorine-based dry etching (Cl / O-based) for patterning the light-shielding film 15 made of simple chromium or a chromium compound may be known conditions used for removing a chromium compound film, and in addition to chlorine gas and oxygen gas, an inert gas such as nitrogen gas or helium gas may be mixed as necessary. The phase shift film 14 located under the light-shielding film 15 is resistant to the oxygen-containing chlorine-based dry etching (Cl / O-based), and therefore remains without being removed or patterned in this process.

[0050] In the step of FIG. 6(d), the conditions for the fluorine-based dry etching (F-based) for patterning the phase shift film 14 may be known conditions that have been used for dry etching silicon-based compound films, tantalum compound films, molybdenum compound films, or the like. CF is used as the fluorine-based gas. 4 Or C 2 F 6 or Sci-Fi 6 is generally used, and active gas such as oxygen or inert gas such as nitrogen gas or helium gas may be mixed as necessary. In the case of Fig. 6(d), the light-shielding film 15 or resist pattern 16 located on the upper layer of the phase shift film 14 is resistant to fluorine-based dry etching (F-based), so it is not removed or patterned in this process and remains. In Fig. 6(d), it is generally used to simultaneously dig into the substrate 11 by about 1 nm to 3 nm to prevent the phase shift film 14 from being removed and to fine-tune the phase difference.

[0051] 6(f), the conditions for the oxygen-containing chlorine-based dry etching (Cl / O-based) for removing the light-shielding film 15 may be known conditions that have been used for removing chromium compound films, and in addition to chlorine gas and oxygen gas, an inert gas such as nitrogen gas or helium gas may be mixed as necessary. Both the phase shift film 14 and the substrate 11 located below the light-shielding film 15 are resistant to the oxygen-containing chlorine-based dry etching (Cl / O-based), and therefore remain without being removed or patterned in this process.

[0052] (Modification) In this embodiment, the surface of the phase layer 12 that has been side-etched by BS, i.e., the shape of the side-etched surface, is inclined at a constant rate from the surface side of the phase layer 12 toward the substrate 11 side, has been described using Figures 3 to 5, but the present invention is not limited to this. As shown in Figures 7(a) to 7(c), for example, the shape of the side-etched surface may be curved. As shown in Figures 7(a) and 7(b), for example, the side-etched amount (width of the side-etching BS) BW may be largest on the upper surface side of the phase layer 12, or may be largest in the center part of the phase layer 12 as shown in Figure 7(c). Note that the protective layer BH is omitted in Figures 7(a) to 7(c).

[0053] [Example] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0054] Example 1 A phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 14 nm on a quartz substrate using a DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. The composition of this phase layer was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic percentage). A protective layer made of tantalum and oxygen was deposited on this phase layer with a thickness of 2 nm using a DC sputtering device. The target was tantalum, and the sputtering gas was argon and oxygen. The composition of this protective layer was analyzed by ESCA and found to be Ta:O=35:65 (atomic percentage).

[0055] In addition, a pair of laminated films composed of the thus formed phase layer and protective layer was laminated in five layers, that is, five layers of phase layers with a thickness of 14 nm and five layers of protective layers with a thickness of 2 nm were alternately laminated, and the total thickness of the phase layers was 70 nm, the total thickness of the protective layers was 10 nm, and the total thickness (thickness) of the phase layers and protective layers was 80 nm, to form a multilayer laminated film, which was a phase shift film (multilayer phase shift film). In addition, this phase shift film had a transmittance of 5% for the exposure light and a phase difference of 177 degrees. Next, a lower light-shielding film made of chromium, oxygen, and nitrogen was deposited to a thickness of 30 nm on the protective layer located on the outermost (top) layer of this phase shift film using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this lower light-shielding film was analyzed by ESCA and found to be Cr:O:N=50:30:20 (atomic percentage ratio). Next, a DC sputtering device was used to deposit an upper light-shielding film made of chromium, oxygen, and nitrogen on the lower light-shielding film to a thickness of 20 nm. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of the upper light-shielding film was analyzed by ESCA and found to be Cr:O:N=45:45:10 (atomic percentage). The phase shift mask blank according to Example 1 thus formed had an OD (Optical Density) value of 3.

[0056] Next, a negative chemically amplified electron beam resist was spin-coated on the upper light-shielding film to a thickness of 160 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern. Next, the upper and lower light-shielding films were patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching apparatus was used to pattern the phase shift film, which was composed of five alternate layers of protective layers and phase layers. The etching gas was CF 4and oxygen were used, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0057] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, each light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film (lower light-shielding film). In this manner, the phase shift mask of Example 1 was obtained. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 110 kJ / cm 2 It was.

[0058] The "dose at which haze occurs due to accelerated exposure" means that the larger the value, the less likely haze is to occur. 2 If the dose is 80 kJ / cm or more (evaluated as "△" in the table below), there is no problem in using the phase shift mask. 2 If the dose is 100 kJ / cm or more (evaluated as "○" in the table below), it is excellent for use with a phase shift mask. 2 If the dose is 70 kJ / cm or higher (evaluated as "◎" in the table below), it can be said to be a phase shift mask that is extremely unlikely to cause haze. 2 If the haze density is less than 100%, which is evaluated as "X" in the table below, it can be said that the occurrence of haze cannot be ignored when using a phase shift mask. From the above measurement results, in the case of the phase shift mask of Example 1, the dose is 110 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0059] Next, this phase shift mask was subjected to electron beam correction, as will be described below. (How to fix) Next, a method for correcting phase shift mask 100 with an electron beam will be described with reference to FIGS. Fig. 8 shows an enlarged view of a portion of phase shift film 14 in phase shift mask 100. More specifically, Fig. 8(a) is a schematic plan view showing the structure of phase shift mask 100 according to this embodiment before the repair process, and Fig. 8(b) is a schematic cross-sectional view showing the structure of phase shift mask 100 according to this embodiment before the repair process. Hereinafter, a specific method will be described for performing electron beam correction etching on the phase shift film pattern 17 (17a) formed by dry etching using the resist pattern 16. In Fig. 8(a), "L" indicates the region where the phase shift film 14 is formed, and "S" indicates the region where the transparent substrate 11 is exposed.

[0060] First, as shown in FIG. 9, the protective layer 13, which is the outermost layer, is irradiated with an electron beam irradiator (MeRiT MG45: manufactured by Carl Zeiss) in a fluorine-based gas atmosphere, for example, a gas atmosphere consisting of fluorine and xenon (XeF 2 ) was irradiated with an electron beam to perform electron beam correction etching. The flow rate of the fluorine-based gas at this time was controlled by a cold trap technique controlled by temperature. In this example, the temperature of the fluorine-based gas was set to 0°C (hereinafter referred to as the controlled temperature). The EB current was set to 50 pA, and the EB acceleration voltage was set to 1 kV.

[0061] Next, as shown in FIG. 10, the phase layer 12, which is the second layer from the top layer, was irradiated with an electron beam in a fluorine-based gas atmosphere using the same device at a controlled temperature of 0° C., and electron beam correction etching was performed in the same manner as the electron beam correction etching of the uppermost protective layer 13. The above steps were repeated to obtain a phase shift mask 100 in which the entire phase shift film 14 was electron beam correction etching, as shown in FIG. 11. The amount of side etching BS at that time (side etching amount BW) was measured by measuring the line width with an SEM (LWM9045: manufactured by ADVANTEST Co., Ltd.) and confirmed to be less than 1 nm. In addition, the Qz etching selectivity during the electron beam correction etching was confirmed to be 1.7. Here, the "Qz etching selectivity" indicates the ratio of the correction etching rate of the protective layer and phase layer (correction etching rate for the entire phase shift film 14) to the correction etching rate of the quartz (Qz) substrate. In Example 1, the selection ratio between the protective layer 13 and the phase layer 14 was 5.4.

[0062] For reference, the corrected etching rates of the protective layer and the phase layer, and the etching rate ratio of the protective layer to the phase layer (corrected etching rate of the protective layer / corrected etching rate of the phase layer) are shown in each table. If the etching rate ratio of the protective layer to the phase layer is 1 or more, it means that the corrected etching rate of the protective layer when corrected by electron beam is larger than the corrected etching rate of the phase layer when corrected by electron beam.

[0063] The smaller the value of the "amount of side etching BS (side etching amount BW)" is, the higher the transfer performance is. If the side etching amount BW is 5 nm or less (evaluated as "○" in the table below), the transfer performance of the phase shift mask is sufficient, and if the side etching amount BW is 1 nm or less (evaluated as "◎" in the table below), the phase shift mask can be said to have extremely high transfer performance. Note that if the side etching amount BW is more than 5 nm (evaluated as "△" in the table below), it can be said that it is difficult to obtain sufficient transfer performance when using a phase shift mask. From the above measurement results, it was confirmed that the phase shift mask of Example 1 has an excellent transfer performance since the side etching amount BW is 1 nm.

[0064] The "Qz etching selectivity" means that the higher the value, the easier the electron beam correction etching of the phase shift film. If the Qz etching selectivity is 1.2 or more (evaluated as "○" in the table below), the phase shift film 14 is easy to correct with an electron beam, and if the Qz etching selectivity is 1.5 or more (evaluated as "◎" in the table below), it can be said that the phase shift mask (phase shift film) is extremely easy to correct with an electron beam. Note that if the Qz etching selectivity is less than 1.2 (evaluated as "△" in the table below), it can be said that the phase shift mask (phase shift film) is difficult to correct with an electron beam. From the above measurement results, it was confirmed that the phase shift mask of Example 1 has a Qz etching selectivity of 1.7, and therefore electron beam correction of the phase shift mask (phase shift film) is extremely easy.

[0065] Example 2 A phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 15 nm on a quartz substrate using a DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. The composition of this phase layer was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic percentage). A protective layer made of tantalum and nitrogen was deposited on this phase layer with a thickness of 2 nm using a DC sputtering device. The target was tantalum, and the sputtering gas was argon and nitrogen. The composition of this protective layer was analyzed by ESCA and found to be Ta:N=80:20 (atomic percentage).

[0066] In addition, a multi-layer laminate film consisting of a pair of the phase layer and the protective layer thus formed was formed by stacking five layers, that is, five layers of phase layers with a thickness of 15 nm and five layers of protective layers with a thickness of 2 nm alternately, the total thickness of the phase layers was 75 nm, the total thickness of the protective layers was 10 nm, and the total thickness (thickness) of the phase layers and the protective layers was 85 nm, to form a phase shift film (multi-layer phase shift film). In addition, this phase shift film had a transmittance of 5% for the exposure light and a phase difference of 177 degrees. Next, a lower light-shielding film made of chromium, oxygen, and nitrogen was deposited to a thickness of 30 nm on the protective layer located on the outermost (top) layer of this phase shift film using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this lower light-shielding film was analyzed by ESCA and found to be Cr:O:N=50:30:20 (atomic percentage ratio).

[0067] Next, a DC sputtering device was used to deposit an upper light-shielding film made of chromium, oxygen, and nitrogen on the lower light-shielding film to a thickness of 20 nm. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of the upper light-shielding film was analyzed by ESCA and found to be Cr:O:N=45:45:10 (atomic percentage). The phase shift mask blank according to Example 2 thus formed had an OD (Optical Density) value of 3. Next, a negative chemically amplified electron beam resist was spin-coated on the upper light-shielding film to a thickness of 160 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0068] Next, the upper and lower light-shielding films were patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching apparatus was used to pattern the phase shift film, which was composed of five alternate layers of protective layers and phase layers. The etching gas was CF 4 and oxygen were used, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0069] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, each light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film (lower light-shielding film). In this manner, the phase shift mask according to the second embodiment was obtained. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 90 kJ / cm 2 It was. From the above results, in the case of the phase shift mask of Example 2, the dose is 90 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0070] Next, this phase shift mask was subjected to electron beam correction, and the side etching amount BW was measured and found to be 2 nm. From the above results, it was confirmed that the phase shift mask of Example 2 has a sufficient transfer performance since the side etching amount BW is 2 nm. In addition, the Qz etching selectivity of this phase shift mask in electron beam repair was measured and found to be 1.9. From the above results, it was confirmed that the phase shift mask of Example 2 has a Qz etching selectivity of 1.9, and therefore electron beam correction of the phase shift mask (phase shift film) is extremely easy. In Example 2, the selection ratio between the protective layer 13 and the phase layer 14 was 5.7.

[0071] Example 3 A phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 16 nm on a quartz substrate using a DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. The composition of this phase layer was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic percentage). A protective layer made of tungsten and oxygen was deposited on this phase layer with a thickness of 2 nm using a DC sputtering device. The target was tungsten, and the sputtering gas was argon and oxygen. The composition of this protective layer was analyzed by ESCA and found to be W:O=25:75 (atomic %).

[0072] In addition, a multi-layer laminate film consisting of a pair of the phase layer and the protective layer thus formed was formed by stacking five layers, that is, five layers of phase layers with a thickness of 16 nm and five layers of protective layers with a thickness of 2 nm alternately, the total thickness of the phase layers was 80 nm, the total thickness of the protective layers was 10 nm, and the total thickness (thickness) of the phase layers and the protective layers was 90 nm, to form a phase shift film (multi-layer phase shift film). In addition, this phase shift film had a transmittance of 5% for the exposure light and a phase difference of 177 degrees. Next, a lower light-shielding film made of chromium, oxygen, and nitrogen was deposited to a thickness of 30 nm on the protective layer located on the outermost (top) layer of this phase shift film using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this lower light-shielding film was analyzed by ESCA and found to be Cr:O:N=50:30:20 (atomic percentage ratio).

[0073] Next, a DC sputtering device was used to deposit an upper light-shielding film made of chromium, oxygen, and nitrogen on the lower light-shielding film to a thickness of 20 nm. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of the upper light-shielding film was analyzed by ESCA and found to be Cr:O:N=45:45:10 (atomic percentage). The phase shift mask blank according to Example 3 thus formed had an OD (Optical Density) value of 3. Next, a negative chemically amplified electron beam resist was spin-coated on the upper light-shielding film to a thickness of 160 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0074] Next, the upper and lower light-shielding films were patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching apparatus was used to pattern the phase shift film, which was composed of five alternate layers of protective layers and phase layers. The etching gas was CF 4 and oxygen were used, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0075] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, each light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film (lower light-shielding film). In this manner, the phase shift mask of Example 3 was obtained. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 75 kJ / cm 2 It was. From the above results, in the case of the phase shift mask of Example 3, the dose amount is 75 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0076] Next, this phase shift mask was subjected to electron beam correction, and the side etching amount BW was measured and found to be 3 nm. From the above results, it was confirmed that the phase shift mask of Example 3 has a sufficient transfer performance since the side etching amount BW is 3 nm. In addition, the Qz etching selectivity of this phase shift mask in electron beam correction was measured and found to be 1.4. From the above results, it was confirmed that the phase shift mask of Example 3 has a Qz etching selectivity of 1.4, and therefore electron beam correction of the phase shift mask (phase shift film) is extremely easy. In Example 3, the selection ratio between the protective layer 13 and the phase layer 14 was 4.0.

[0077] Example 4 A phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 15 nm on a quartz substrate using a DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. The composition of this phase layer was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic percentage). A protective layer consisting of tellurium and oxygen was deposited on this phase layer with a thickness of 2 nm using a DC sputtering device. Tellurium was used as the target, and argon and oxygen were used as the sputtering gas. The composition of this protective layer was analyzed by ESCA and found to be Te:O=35:65 (atomic percentage).

[0078] In addition, a multi-layer laminate film consisting of a pair of the phase layer and the protective layer thus formed was formed by stacking five layers, that is, five layers of phase layers with a thickness of 15 nm and five layers of protective layers with a thickness of 2 nm alternately, the total thickness of the phase layers was 75 nm, the total thickness of the protective layers was 10 nm, and the total thickness (thickness) of the phase layers and the protective layers was 85 nm, to form a phase shift film (multi-layer phase shift film). In addition, this phase shift film had a transmittance of 5% for the exposure light and a phase difference of 177 degrees. Next, a lower light-shielding film made of chromium, oxygen, and nitrogen was deposited to a thickness of 30 nm on the protective layer located on the outermost (top) layer of this phase shift film using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this lower light-shielding film was analyzed by ESCA and found to be Cr:O:N=50:30:20 (atomic percentage ratio).

[0079] Next, a DC sputtering device was used to deposit an upper light-shielding film made of chromium, oxygen, and nitrogen on the lower light-shielding film to a thickness of 20 nm. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of the upper light-shielding film was analyzed by ESCA and found to be Cr:O:N=45:45:10 (atomic percentage). The phase shift mask blank according to Example 4 thus formed had an OD (Optical Density) value of 3. Next, a negative chemically amplified electron beam resist was spin-coated on the upper light-shielding film to a thickness of 160 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern.

[0080] Next, the upper and lower light-shielding films were patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%. Next, a dry etching apparatus was used to pattern the phase shift film, which was composed of five alternate layers of protective layers and phase layers. The etching gas was CF 4 and oxygen were used, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm.

[0081] Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, each light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film (lower light-shielding film). In this manner, the phase shift mask of Example 4 was obtained. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 71 kJ / cm 2 It was. From the above results, in the case of the phase shift mask of Example 4, the dose amount is 71 kJ / cm 2 Therefore, it was confirmed that the occurrence of haze can be reduced.

[0082] Next, this phase shift mask was subjected to electron beam correction, and the side etching amount BW was measured and found to be 2 nm. From the above results, it was confirmed that the phase shift mask of Example 4 has a sufficient transfer performance since the side etching amount BW is 2 nm. In addition, the Qz etching selectivity of this phase shift mask in electron beam correction was measured and found to be 1.3. From the above results, it was confirmed that the phase shift mask of Example 4 has a Qz etching selectivity of 1.3, and therefore the electron beam correction of the phase shift mask (phase shift film) is extremely easy. In Example 4, the selection ratio between the protective layer 13 and the phase layer 14 was 2.6.

[0083] Comparative Example 1 A phase layer consisting of silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 75 nm on a quartz substrate using a DC sputtering device with two targets. The targets used were molybdenum and silicon, and the sputtering gases used were argon, oxygen, and nitrogen. The composition of this phase layer was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic percentage).

[0084] Next, a lower light-shielding film made of chromium, oxygen, and nitrogen was deposited on the phase layer with a thickness of 30 nm using a DC sputtering device. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of this light-shielding film was analyzed by ESCA and found to be Cr:O:N = 50:30:20 (atomic percentage). Next, a DC sputtering device was used to deposit an upper light-shielding film made of chromium, oxygen, and nitrogen on the lower light-shielding film to a thickness of 20 nm. Chromium was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gas. The composition of the upper light-shielding film was analyzed by ESCA and found to be Cr:O:N=45:45:10 (atomic percentage). The phase shift mask blank according to Comparative Example 1 thus formed had an OD (Optical Density) value of 3.

[0085] Next, a negative chemically amplified electron beam resist was spin-coated on the upper light-shielding film to a thickness of 160 nm, and a pattern was formed with a dose of 35 μC / cm 2 The resist was patterned by electron beam drawing at 800 .ANG., heat-treated at 110.degree. C. for 10 minutes, and developed by paddle development for 90 seconds to form a resist pattern. Next, the upper and lower light-shielding films were patterned using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Overetching was performed to 100%.

[0086] Next, a dry etching apparatus was used to pattern the phase shift film consisting of only the phase layer. The etching gas was CF 4 and oxygen were used, and the gas pressure was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped when the quartz substrate was dug to an average depth of 3 nm. Next, the resist pattern was stripped and cleaned by washing with sulfuric acid and water. Next, each light-shielding film was removed using a dry etching device. Chlorine, oxygen, and helium were used as the etching gas, and the gas pressure was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Overetching was performed by 200%. During this process, no damage was caused to the phase shift film and the quartz substrate located below the light-shielding film (lower light-shielding film).

[0087] In this way, a phase shift mask according to Comparative Example 1 was obtained. That is, the phase shift mask according to Comparative Example 1 is a phase shift mask that does not have the protective layer formed in Examples 1 to 4, and does not have a multilayer phase shift film formed by alternately stacking five protective layers and phase layers formed in Examples 1 to 4. Next, the dose at which haze occurred due to accelerated exposure was measured for this phase shift mask, and it was found to be 58 kJ / cm 2 It was. From the above results, in the phase shift mask of Comparative Example 1, the dose was 58 kJ / cm 2 Therefore, it was confirmed that the generation of haze could not be sufficiently reduced.

[0088] Next, this phase shift mask was subjected to electron beam correction, and the side etching amount BW was measured and found to be 7 nm. From the above results, it was confirmed that the phase shift mask of Comparative Example 1 does not have sufficient transfer performance because the side etching amount BW is 7 nm. In addition, the Qz etching selectivity of this phase shift mask in electron beam correction was measured and found to be 1.1. From the above results, it was confirmed that in the phase shift mask of Comparative Example 1, the Qz etching selectivity was 1.1, and therefore electron beam correction of the phase shift mask (phase shift film) was difficult.

[0089] The evaluation results of the above-mentioned Examples 1 to 3 and Comparative Example 1 are shown in Tables 1 and 2. In this example, the haze resistance (dose at which haze occurs), repair processability (Qz etching selectivity), cross-sectional shape (amount of side etching), and transfer performance were each evaluated. The dose at which haze occurs is 70 kJ / cm 2 " or higher, there is no problem with use and it is considered to have passed. Regarding the amount of side etching, if the amount is "5 nm" or less, there is no problem in use and it is therefore rated as passing. Regarding the corrected etching rate ratio, if the amount was "1.2" or more, there was no problem in use and it was therefore rated as passed. In Tables 1 and 2, the transfer performance is indicated as "○" when there is little projection effect and there is no problem with the transfer performance in use, and as "△" when the projection effect cannot be ignored and improvement of the transfer performance is desired in use. The "etching time (min.) of the phase shift film (protective layer and phase layer)" in Table 1 is a value calculated using each Qz etching selectivity ratio, assuming that the "etching time (min.) of the phase shift film (phase layer)" in Table 2 is 30 (min.).

[0090] [Table 1]

[0091] [Table 2]

[0092] As described above, it is found that forming a protective layer on a phase layer and forming a multilayer phase shift film in which phase layers and protective layers are alternately stacked multiple times is effective in reducing the amount of haze generated in a phase shift mask. It has also been found that forming a protective layer on a phase layer and forming a multilayer phase shift film by alternately stacking multiple phase layers and protective layers is effective in facilitating electron beam correction in a phase shift mask (phase shift film). Furthermore, it is found that forming a protective layer on a phase layer and forming a multilayer phase shift film by alternately stacking multiple phase layers and protective layers is effective in improving the transfer performance of a phase shift mask (phase shift film).

[0093] The phase shift mask blank of the present invention and the phase shift mask produced using the same have been described above using the above examples, but the above examples are merely examples for carrying out the present invention, and the present invention is not limited to these. Furthermore, modifications of these examples are within the scope of the present invention, and it is self-evident from the above description that various other embodiments are possible within the scope of the present invention. [Industrial Applicability]

[0094] In the present invention, the composition, film thickness, and layer structure of the phase shift mask blank, as well as the manufacturing process and conditions for a phase shift mask using the same are selected within appropriate ranges, making it possible to provide a phase shift mask in which fine patterns are formed with high precision and which is suitable for the manufacture of logic devices of 28 nm or less, or memory devices of 30 nm or less. [Explanation of symbols]

[0095] 10. Phase shift mask blank 11... Substrate (substrate) transparent to the exposure wavelength 12...Phase layer (phase difference transmittance adjustment layer) 13 Protective layer (gas permeable protective layer) 14 Phase shift film (multilayer phase shift film) 15. Light-shielding film 16. Resist pattern 17 Phase shift film pattern 17a Phase shift film pattern 17b: Electron beam etching area 100 Phase shift mask BS...Side Etching BH... Protective layer (etching resistant film) BW: Side etching amount (width of side etching) L: Region where phase shift film is formed S: Area where the transparent substrate is exposed

Claims

1. A phase shift mask blank used for producing a phase shift mask to which exposure light having a wavelength of 200 nm or less is applied, A transparent substrate, a phase shift film formed on the transparent substrate, and a light-shielding film formed on the phase shift film, The phase shift film is a multi-layer phase shift film in which a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for a transmitted exposure light and a gas permeable protective layer preventing gas from permeating the phase difference transmittance adjusting layer are alternately laminated in a plurality of layers, A phase shift mask blank, characterized in that a correction etching rate of the gas permeable protective layer during electron beam correction is greater than that of the phase difference transmittance adjusting layer.

2. 2. The phase shift mask blank according to claim 1, wherein the phase shift film is resistant to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

3. the retardation transmittance adjusting layer contains silicon and at least one selected from a transition metal, nitrogen, oxygen, and carbon; 3. The phase shift mask blank according to claim 1, wherein the transition metal is at least one selected from the group consisting of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

4. The thickness of each of the phase difference transmittance adjusting layers is 0.5 nm or more; 4. The phase shift mask blank according to claim 3, wherein a total of the thicknesses of the retardation transmittance adjusting layers is greater than a total of the thicknesses of the gas permeable protective layers.

5. 5. The phase shift mask blank according to claim 1, wherein the gas permeable protective layer contains at least one selected from the group consisting of tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, and tellurium compounds.

6. The thickness of each of the gas permeable protective layers is 0.5 nm or more; 6. The phase shift mask blank according to claim 5, wherein the total thickness of each of the gas permeable protective layers is 30 nm or less.

7. 7. The phase shift mask blank according to claim 5, wherein the tantalum compound contains tantalum and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

8. 7. The phase shift mask blank according to claim 5, wherein the tungsten compound contains tungsten and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

9. 7. The phase shift mask blank according to claim 5, wherein the tellurium compound contains tellurium and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

10. 10. The phase shift mask blank according to claim 1, wherein an outermost layer of the phase shift film is the gas permeable protective layer.

11. A phase shift mask having a circuit pattern to which exposure light having a wavelength of 200 nm or less is applied, A transparent substrate, a phase shift film formed on the transparent substrate, and a light-shielding film formed on the phase shift film, The phase shift film is a multi-layer phase shift film in which a phase difference transmittance adjusting layer capable of adjusting a predetermined amount of phase and transmittance for a transmitted exposure light and a gas permeable protective layer preventing gas from permeating the phase difference transmittance adjusting layer are alternately laminated in a plurality of layers, A phase shift mask, characterized in that a correction etching rate of said gas permeable protective layer during electron beam correction is greater than that of said phase difference transmittance adjusting layer.

12. 12. The phase shift mask according to claim 11, wherein the phase shift film is resistant to oxygen-containing chlorine-based etching (Cl / O-based) and can be etched with fluorine-based etching (F-based).

13. the retardation transmittance adjusting layer contains silicon and at least one selected from a transition metal, nitrogen, oxygen, and carbon; 13. The phase shift mask according to claim 11, wherein the transition metal is at least one selected from the group consisting of molybdenum, titanium, vanadium, cobalt, nickel, zirconium, niobium, and hafnium.

14. The thickness of each of the phase difference transmittance adjusting layers is 0.5 nm or more; 14. The phase shift mask according to claim 13, wherein a total of the thicknesses of the phase difference transmittance adjusting layers is greater than a total of the thicknesses of the gas permeable protective layers.

15. 15. The phase shift mask according to claim 11, wherein the gas permeable protective layer contains at least one selected from the group consisting of tantalum metal, tantalum compounds, tungsten metal, tungsten compounds, tellurium metal, and tellurium compounds.

16. The thickness of each of the gas permeable protective layers is 0.5 nm or more; 16. The phase shift mask according to claim 15, wherein the total thickness of each of the gas permeable protective layers is 30 nm or less.

17. 17. The phase shift mask according to claim 15, wherein the tantalum compound contains tantalum and at least one element selected from the group consisting of oxygen, nitrogen, and carbon.

18. 17. The phase shift mask according to claim 15, wherein the tungsten compound contains tungsten and at least one element selected from the group consisting of oxygen, nitrogen and carbon.

19. 17. The phase shift mask according to claim 15, wherein the tellurium compound contains tellurium and at least one element selected from the group consisting of oxygen, nitrogen and carbon.

20. 20. The phase shift mask according to claim 11, wherein an outermost layer of the phase shift film is the gas permeable protective layer.

21. A method for producing a phase shift mask using the phase shift mask blank according to any one of claims 1 to 10, comprising the steps of: forming a light-shielding film on the phase shift film; forming a resist pattern on the light-shielding film; forming a pattern on the light-shielding film by oxygen-containing chlorine-based etching (Cl / O-based) after forming the resist pattern; forming a pattern on the light-shielding film, and then forming a pattern on the phase shift film by fluorine-based etching (F-based); removing the resist pattern after forming a pattern in the phase shift film; and after removing the resist pattern, removing the light-shielding film from above the phase shift film by oxygen-containing chlorine-based etching (Cl / O-based).

22. 21. A method for correcting a phase shift mask according to claim 11 by electron beam correction etching, comprising: a step of carrying out a surface oxidation treatment on each of said gas permeable protective layers immediately before repairing said gas permeable protective layers;

Citation Information

Patent Citations

  • Method for manufacturing photomask

    JP2015184453A

  • Halftone phase shift photomask blank and method for manufacturing the same

    JP2016035559A

  • Method of manufacturing photomask blank, photomask blank, method of manufacturing photomask, photomask, and photomask metal target

    JP2018173621A

  • Method for manufacturing a photomask blank, and a method for manufacturing a photomask blank and a photomask, and a photomask

    JP4579728B2

  • Reflective mask blank, reflective mask and method for manufacturing semiconductor device

    WO2017169658A1